Customer Experience Management (CEM) Supports the Quality of School Based on NFC - Dendy Jonas Managas; Ageng Setiani Rafika; Dedy Prasetya Kristiadi; Pramita Retno Ayuning Tyas (IJISTECH (International Journal of Information System and Technology), 2021)
Schools as providers of educational services are a gateway to the progress of a nation. Many prospective students look for schools with good quality in order to get something that they aspire to. While the reference for assessing school services for prospective students can only be known from students who have graduated or through poster media. Meanwhile, the assessment of student experience only refers to personal opinions and only one factor such as teaching services or administration. Each student has a different argument about school services. This study will explain the creation of a framework for determining service levels in NFC-based schools. Evaluation of services in schools using information technology through smartphone applications connected to the computer provided at the information service desk. The information generated in the form of evaluating educational services in schools aims to improve the quality of learning and academic administrative services. Furthermore, the information generated will be made a report by the data processor addressed to the leadership. With this service, it is expected that there will be an increase in the quality of education and learning services that are able to produce quality graduates and can become information and references for prospective students in choosing schools as a reference for educational services